Genetic counselor review of genetic test orders in a reference laboratory reduces unnecessary testing. Issue 5 (24th March 2014) - Miller, Christine E.; Krautscheid, Patti; Baldwin, Erin E.; Tvrdik, Tatiana; Openshaw, Amanda S.; Hart, Kim; LaGrave, Danielle
<x xml:space="preserve">Abstract</x> Genetic tests are routinely ordered by health care providers (HCPs) within a wide range of medical specialties. Many providers have limited knowledge or experience with ordering and interpreting genetic tests; thus, test order errors are common. Rigorous review of genetic test orders by genetic counselors (GCs) can provide a direct financial benefit to medical institutions, patients and insurers. GCs at ARUP (Associated Regional University Pathologists) Laboratories routinely perform a preanalytic assessment of complex molecular genetic test orders that includes reviewing clinical and family history information and considering the clinical utility and cost‐effectiveness of ordered tests. GCs contact the ordering institution and/or HCP as needed to collect additional clinical information and confirm the test order or suggest alternative testing based on the provided information. A retrospective review of the GC‐facilitated test changes over a 21‐month period at ARUP laboratories was performed. Approximately 26% of all requests for complex genetic tests assessing germ line mutations were changed following GC review. Testing fees associated with canceled tests were summed to estimate the cost‐savings resulting from GC‐facilitated test reviews. The test review process resulted in an average reduction in charges to the referring institutions of $48, 000.00 per month. GC review of genetic test orders for appropriateness and clinical utility reduces healthcare costs to hospitals, insurers, and patients. © 2014 Wiley Periodicals, Inc.